Mowing Did Not Alleviate the Negative Effect of Nitrogen Addition on the Arbuscular Mycorrhizal Fungal Community in a Temperate Meadow Grassland - Qin, Siqi; Yang, Guojiao; Zhang, Yang; Song, Meixia; Sun, Lu; Cui, Yangzhe; Dong, Jibin; Wang, Ning; Liu, Xiao; Zheng, Peiming; Wang, Renqing (Frontiers in Plant Science, 2022)
As nitrogen deposition intensifies under global climate change, understanding the responses of arbuscular mycorrhizal (AM) fungi to nitrogen deposition and the associated mechanisms is critical for terrestrial ecosystems. In this study, the effects of nitrogen addition and mowing on AM fungal communities in soil and mixed roots were investigated in an Inner Mongolia grassland. The results showed that nitrogen addition reduced the α-diversity of AM fungi in soil rather than that of root. Besides, nitrogen addition altered the composition of AM fungal community in soil. Soil pH and inorganic nitrogen content were the main causes of changes in AM fungal communities affected by nitrogen addition. In contrast, while mowing may reduce the negative effects of nitrogen addition on the richness and diversity of plants by alleviating light limitation, it could not do so with the negative effects on AM fungal communities. Furthermore, AM fungal communities clustered phylogenetically in all treatments in both soil and roots, indicating that environmental filtering is the main driving force for AM fungal community assembly. Our results highlight the different responses of AM fungi in the soil and roots of a grassland ecosystem to nitrogen addition and mowing. The study will improve our understanding of the effects of nitrogen deposition on the function of ecosystem.